Interfacial Assembly of Nanoparticles with Fluorous-Tagged Organic Molecules - Lu, Zhiqiang; Zhou, Xin; Hu, Sheng; Shu, Xin; Tian, Yuan; Zhu, Jin (Journal of physical chemistry. C, 2010)
Nanoparticles have been the subject of intensive study recently due to their interesting size- and morphology-dependent functional attributes. The assembly of nanoparticles into higher-ordered structures provides an exciting venue for the generation of novel collective properties. Herein, a versatile, fluorous tag-based method for the assembly of nanoparticles has been developed, leading to the formation of nanoparticle networks at either the gas−liquid, liquid−liquid, or solid−liquid interface. This capability would provide us with a key tool to probe the structures, dynamics, functions, and utilities of nanoparticle assemblies in a variety of environmental settings. Characterization with transmission electron microscopy, scanning electron microscopy, dynamic light scattering, and UV−vis extinction spectroscopy allowed us to gain tremendous insight into this significant process. The method can be readily extended to nanoparticle building blocks of other compositions, and novel functions could be harnessed through this superior strategy.